Laboratory Diagnosis of COVID-19 in China: A review of challenging cases and analysis (2020)
Since the initial emergence of coronavirus disease 2019 (COVID-19) in Wuhan, Hubei province, China, a rapid spread of the disease occurred around the world, rising to become an international global health concern at pandemic level. In the face of this medical challenge threatening humans, the development of rapid and accurate methods for early screening and diagnosis of COVID-19 became crucial to containing the emerging public health threat, and prevent further spread within the population. Despite the large number of COVID-19 confirmed cases in China, some problematic cases with inconsistent laboratory testing results, were reported. Specifically, a high false-negative rate of 41% on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection by real-time reverse transcription-polymerase chain reaction (qRT-PCR) assays was observed in China. Although serological testing has been applied worldwide as a complementary method to help identify SARS-CoV-2, several limitations on its use have been reported in China. Therefore, the use of both qRT-PCR and serological testing in the diagnosis of COVID-19 in China and elsewhere, presented considerable challenges, but when used in combination, can be valuable tools in the fight against COVID-19. In this review, we give an overview of the advantages and disadvantages of different molecular techniques for SARS-CoV-2 detection that are currently used in several labs, including qRT-PCR, gene sequencing, loop-mediated isothermal amplification (LAMP), nucleic acid mass spectrometry (MS), and gene editing technique based on clustered regularly interspaced short palindromic repeats (CRISPR/Cas13) system. Then we mainly review and analyze some causes of false-negative qRT-PCR results, and how to resolve some of the diagnostic dilemma.